Palliative care experience of US adult nephrology fellows: a national survey. (17th September 2013) - Shah, Hitesh H.; Monga, Divya; Caperna, April; Jhaveri, Kenar D.
Abstract: Palliative care (PC) training and experience of United States (US) adult nephrology fellows was not known. It was also not clear whether nephrology fellows in the US undergo formal training in PC medicine during fellowship. To gain a better understanding of the clinical training and experience of US adult nephrology fellows in PC medicine, we conducted a national survey in March 2012. An anonymous on-line survey was sent to US adult nephrology fellows via nephrology fellowship training program directors. Fellows were asked several PC medicine experience and training questions. A total of 105 US adult nephrology fellows responded to our survey (11% response rate). Majority of the respondents (94%) were from university-based fellowship programs. Over two-thirds (72%) of the fellows had no formal PC medicine rotation during their medical school. Half (53%) of the respondents had no formal PC elective experience during residency. Although nearly 90% of the fellows had a division or department of PC medicine at their institution, only 46.9% had formal didactic PC medicine experience. Over 80% of the respondent's program did not offer formal clinical training or rotation in PC medicine during fellowship. While 90% of the responding fellows felt most comfortable with either writing dialysis orders in the chronic outpatient unit, seeing an ICU consult or writing continuous dialysis orders in the ICU, only 35% of them felt most comfortable "not offering" dialysis to a patient in the ICU with multi-organ failure. Nearly one out of five fellows surveyed felt obligated to offer dialysis to every patient regardless of benefit. Over two-thirds (67%) of the respondents thought that a formal rotation in PC medicine during fellowship would be helpful to them. To enhance clinical competency and confidence in PC medicine, a formal PC rotation during fellowship should be highly considered by nephrology training community.